1989
DOI: 10.3758/bf03205214
|View full text |Cite
|
Sign up to set email alerts
|

The CS− effect in simple conditioning and stimulus selection during development

Abstract: Changes in affect toward a particular stimulus can take place very rapidly through Pavlovian conditioning, if presentation of the conditioned stimulus (CS+) paired with the unconditioned stimulus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…These ontogenetic trends are consistent with those found in the literature. Similar results have been dustrated by Campbell and Campbell (1962) and many others (e.g., Schulenburg, Riccio, & Stikes, 1971) using fear conditioning procedures, researchers employing appetitive tasks (e.g., Spear, Kucharski, & Miller, 1989)) and by investigators examining habituation to various sensory stimuli (e.g., Richardson & Campbell, 199 1;Hayne, Richardson, & Campbell, 1992).…”
Section: Retention (Min)mentioning
confidence: 57%
“…These ontogenetic trends are consistent with those found in the literature. Similar results have been dustrated by Campbell and Campbell (1962) and many others (e.g., Schulenburg, Riccio, & Stikes, 1971) using fear conditioning procedures, researchers employing appetitive tasks (e.g., Spear, Kucharski, & Miller, 1989)) and by investigators examining habituation to various sensory stimuli (e.g., Richardson & Campbell, 199 1;Hayne, Richardson, & Campbell, 1992).…”
Section: Retention (Min)mentioning
confidence: 57%
“…In Pautassi et al, (2005b) a tactile stimulus (CS − ) predicted the initial phase of ethanol intoxication, while the gustatory stimulus (sucrose, CS + ) was presented during a later period of the toxic processes, characterized by peak BALs. Employment of a CS − /CS + Pavlovian strategy is known to facilitate, particularly in young rats, the acquisition of aversive memories otherwise not detected through simple excitatory conditioning procedures that only utilize a CS + (Kucharski et al, 1985 Spear et al, 1989). It should also be noted that prenatal ethanol has been found to ameliorate ethanol-mediated CTA during infancy (Arias and Chotro, 2006b).…”
Section: Conditioned Aversion Mediated By Ethanol In the Preweanlimentioning
confidence: 99%
“…Ontogenetic differences in stimulus selection are evident in a variety of circumstances (for reviews, see Spear & Kucharski, 1984a, 1984bSpear, Kucharski, & Miller, 1989), including a tendency for younger animals to show greater conditioning to "incidental" stimuli present at the time of conditioning. For example, Solheim, Hensler, and Spear (1980) found that a shift in the context from training to testing resulted in a disruption in the performance of active avoidance in young animals that was not evident in adults.…”
mentioning
confidence: 99%